PERSPEKTIF GURU DAN SISWA DALAM IMPLEMENTASI JOYFUL LEARNING PADA PEMBELAJARAN IPAS DI SDN BENTENG 1 GENTRAMASEKDAS - Silvia Khoerun Nisa; Budi Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the perspectives of teachers and students on the implementation of Joyful Learning in science learning at SDN Benteng 1 Gentramasekdas. The study used a qualitative approach with field research. The research subjects consisted of three teachers of grades IV, V, and VI and 80 students. Data collection techniques were conducted through interviews, documentation, and questionnaires. The results of the study indicate that the implementation of Joyful Learning has been running well and has had a positive impact on the science learning process. The implementation of Joyful Learning is reflected in the creation of a conducive learning environment (100%), interactive and harmonious relationships (100%), active involvement (90%), providing meaning and appreciation (100%), varied learning methods (88.75%), and learning satisfaction (95%). This success is supported by the availability of adequate facilities and infrastructure and the creativity of teachers in managing learning. The findings of this study indicate that the implementation of Joyful Learning contributes to creating a fun and meaningful learning experience and encourages student engagement in science learning.